Myocardial work in hypertrophic cardiomyopathy - a new non-invasive parameter for segmental myocardial function?. (4th February 2022) - Batzner, A; Seggewiss, H; Hahn, P; Sahiti, F; Maack, C; Gerull, B; Stoerk, S; Morbach, C
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): DFG Introduction: Hypertrophic cardiomyopathy (HCM) is the most common genetic cardiac disease. Alcohol septal ablation (PTSMA) is an established treatment option for patients with intracavitary obstruction. In non-obstructive patients, measurement of myocardial work (MW) using pressure strain loops was introduced as a new non-invasive tool to estimate myocardial performance. Purpose: In this preliminary study, we compared global constructive work (GCW) and global wasted work (GWW) as well as the respective values for the septal- and lateral-basal segments in HOCM after successful PTSMA and non-obstructive HCM. Methods: We included 12 patients (4 women, mean age 59.1 ± 17.6 years) with non-obstructive (maximal left ventricular gradient <30 mmHg; mean 10.6 ± 6.2 mmHg) HCM. 7 (58%) patients (subgroup A) had successful gradient reduction by PTSMA ≥3 months before analysis, whereas 5 patients had non-obstructive HCM (subgroup B). Using echocardiographic measurements of longitudinal strain and non-invasive measurements of peripheral- and calculated (PWA) central blood pressure (BP) as left ventricular systolic pressure (LVSP), we estimated and compared GCW and GWW as well as constructive work (CW) and wasted work (WW) of septal-basal and lateral-basal segments. Results: In subgroup B, NTproBNP was significant higher than in subgroup A (2050 ± 1957 vs. 552 ± 845 pg/ml; p < 0.05). There were no differences between both subgroups in maximal septal thickness (20.7 ± 2.9 mm (A) vs. 22.2 ± 3.6 mm) and left atrial volume (91.6 ± 33.0 (A) vs. 114.0 ± 49.8 ml (B)). Using the measured peripheral BP as LVSP, GCW (1653 ± 347 (A) mmHg% vs 1641 ± 698mmHg%) and GWW (171 ± 89mmHg% (A) vs. 200 ± 126 mmHg%) showed no differences between both subgroups. Compared to published data of a healthy population, values of GCW were lower and values of GWW higher in HCM. Comparison in segmental analysis in subgroup A showed lower CW in septal-basal than in lateral-basal segments (1032 ± 385mmHg% vs. 1929 ± 699 mmHg%). In the subgroup B the finding was the same pattern (1024 ± 504mmHg% vs. 2301 ± 1069 mmHg%). In contrast, WW showed no difference between basal-septal and lateral-basal segments in both subgroups. Conclusions: Our preliminary data show decreased GCW and increased GWW in HCM patients without obstruction at rest. As expected, we found lower CW in septal-basal segments than lateral-basal in patients after PTSMA with basal-septal-induced therapeutic infarction. Surprisingly, we found the same pattern in non-obstructive HCM patients. This finding might be one pathophysiological reason for not developing LVOT obstruction, which should be investigated in further detail.